2020
DOI: 10.1016/j.lungcan.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of survival following anti-cancer treatment for small cell lung cancer

Abstract: This is a comprehensive analysis of early and late survival following treatments recommended by the European Society of Medical Oncology for small cell lung cancer. Our survival benchmarks can inform the treatment selection process going forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 163 publications
0
18
0
Order By: Relevance
“…Since SCLC has a very short survival time, new treatment strategies are urgently needed. The clinical efficacy of immunotherapies has been observed in patients with refractory or metastatic SCLC [12,[19][20][21][22][23]. The phase II KEYNOTE-158 study [21] showed that the PFS of pembrolizumab for relapsed SCLC was 2.0 months, the median OS was 9.1 months, and the one-year PFS and OS were 16.8% and 40.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since SCLC has a very short survival time, new treatment strategies are urgently needed. The clinical efficacy of immunotherapies has been observed in patients with refractory or metastatic SCLC [12,[19][20][21][22][23]. The phase II KEYNOTE-158 study [21] showed that the PFS of pembrolizumab for relapsed SCLC was 2.0 months, the median OS was 9.1 months, and the one-year PFS and OS were 16.8% and 40.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison a systematic review that examined oneyear survival from mostly clinical trial research estimated 1 year survival to be approximately 73% in LD-SCLC and 38% in ED-SCLC (14). Better survival in clinical trials can be explained by selection bias.…”
Section: One-year Survivalmentioning
confidence: 99%
“…Although the majority of ES-SCLC occur mutation of TP53(90%) and RB1(65%), the target driven gene is not clear, which leads to limited progress in the treatment of ES-SCLC [4]. In the pre-immunotherapy era, platinum based(carboplatin or cisplatin) etoposide chemotherapy has always been the standard-of-care first-line treatment for ES-SCLC [5][6][7], which is associated with poor outcomes (a 5-year survival rate of 6%-7% and median over survival(OS) of approximately10 months) [8][9]. More efficacious first-line therapy is urgently needed to improve this prognosis.…”
Section: Introductionmentioning
confidence: 99%